Leukocytic picture in pediatric Coronavirus Disease-19 infection - Dey, Pranoy; Das, Rhitwika (Indian Journal of Child Health, 2021)
Background: Coronavirus is a large family of enveloped single-stranded zoonotic RNA virus, causes a wide spectrum of disease including Coronavirus disease-2019 (COVID-19). It is a systemic disease where immunological response has been cited as the most important parameter for both COVID-19 related death as well recoveries. Among all the blood parameters, leukocytes play the most important role in mounting an immune response. COVID-19 being a novel virus has enough literature on its leukocytic picture in adult population which is being lacking in pediatrics study. Aim: The aim of the study was to study the leukocyte picture of COVID-19 positive pediatric populations admitted in Assam Medical College and Hospital. Methods: An observational study was conducted on COVID-19 positive pediatrics patients (Age >1 month–12 years) as detected by rapid antigen test/reverse transcription-polymerase chain reaction and whose blood samples could be sent for investigations. Patient’s status and leukocytic picture at the time of admission were studied. They were followed up till discharge. Results: A total 54 COVID-19 positive patients were enrolled in the study. The mean age group was 8±2 years and gender was male predominant. Out of 54 patients enrolled in the study, 38.89% had lymphocytopenia, 25.9% neutropenia, 24% normal blood picture, and 12.96% had leukocytosis. Four patients expired and 50 patients were discharged. Neutropenia was found in 100% of the mortalities. Conclusion: Lymphocytopenia is the most commonly found deranged blood parameter. Neutropenia when found in COVID-19 positive pediatrics population, signify poor prognosis.